Monitoring of a network under DDoS attack for Machine Learning model validation (2022)
The study seeks to validate a machine learning model which is trained to predict cyber attacks. During the process, different tools were installed to monitor the network, process the information captured and extract data in two different environments: network when it was not under attack and network when it was under attack, to study the behavior of the model and to know how efficient it is under these simulated environments.